Tolerance of Phellodendron amurense Bark Extract (Nexrutine®) in Patients with Human Prostate Cancer. (9th September 2014) - Swanson, Gregory P.; Jones, William E.; Ha, Chul S.; Jenkins, Carol A.; Kumar, Addanki Pratap; Basler, Joseph
<x xml:space="preserve">Abstract</x> Phellodendron amurense bark extract (Nexrutine®) has shown a favorable effect on prostate cancer in vivo and in vitro. We evaluated its tolerance in patients undergoing surgery or radiation for prostate cancer. Patients received Nexrutine® orally (500 mg tid) either 1 to 2 months preoperatively or 1 to 2 months prior to and with radiation therapy. Common Terminology Criteria for Adverse Events were used to measure tolerance. In total, 21 patients (9 surgery and 12 radiation) underwent treatment. During the Nexrutine® alone component, there were two transient grade 3 toxicities (hypokalemia and urinary incontinence). There was no grade 4 toxicity. For the combined Nexrutine® and radiation component, no additional patients suffered a grade 3 toxicity. All the toxicities were transient. By the end of the neoadjuvant treatment, 81% of the patients had a decline in prostate‐specific antigen. This is the first report of patients with prostate cancer being treated with P. amurense bark extract, and it was very well tolerated. Toxicities were minimal and self‐limited. This compound can be safely used in further evaluation of a treatment effect on cancer. Copyright © 2014 John Wiley & Sons, Ltd.